Enhanced recovery after surgery in elective cesarean section patients with gestational diabetes mellitus does not lead to glucose-related maternal and neonatal complications - Zhou, Jin; Zhang, Peizhen; Tan, Zhangmin; Li, Chuo; Yao, Lin; He, Tiantian; Hou, Hongyin; Yin, Yuzhu (Frontiers in Endocrinology, 2024)
Objective For elective cesarean section patients with gestational diabetes mellitus (GDM), there is a lack of evidence-based research on the use of enhanced recovery after surgery (ERAS). This study aims to compare the ERAS after-surgery protocol and traditional perioperative management.In this retrospective cohort study, singleton pregnancies with good glucose control GDM, delivered by elective cesarean sections under intravertebral anesthesia at least 37 weeks from January 1 to December 31, 2022, were collected at the Third Affiliated Hospital of Sun Yat-sen University. We divided all enrolled pregnant women and newborns into an ERAS group and a control group (the traditional perioperative management group) based on their adherence to the ERAS protocol. The primary outcome was the preoperative blood glucose level, with an increase of more than 1 mmol/L indicating clinical significance when compared to the control group. The secondary outcome was centered around an adverse composite outcome that affected both mothers and newborns.We collected a total of 161 cases, with 82 in the ERAS group and 79 in the control group.Although the mean preoperative blood glucose level in the ERAS group was significantly higher than in the control group (5.01 ± 1.06 mmol/L vs. 4.45 ± 0.90 mmol/L, p<0.001), the primary outcome revealed that the mean glycemic difference between the groups was 0.47 mmol/L (95% CI 0.15-0.80 mmol/L), which was below the clinically significant difference of 1 mmol/L. For the secondary outcomes, the ERAS group had an 86% lower risk of a composite adverse outcome compared to the control group. This included a 73% lower risk of perioperative maternal hypoglycemia and a 92% lower rate of neonatal hypoglycemia, all adjusted by age, hypertensive disorder of pregnancy, BMI, gestational weeks, primigravidae, primary pregnancy, GDM, surgery duration, and fasting glucose.Implementing a low-dose carbohydrate ERAS in pregnant women with GDM prior to elective cesarean section, compared to traditional perioperative management, does not lead to clinically significant maternal glucose increases and thus glucose-related maternal or neonatal perioperative complications.